Epstein–Barr Virus-Specific Immune Control by Innate Lymphocytes - Münz, Christian (Frontiers in Immunology, 2017)
Epstein Barr virus (EBV) is a potent B cell transforming pathogen in humans. In most persistently EBV infected individuals, potent cytotoxic lymphocyte responses prevent EBV associated pathologies. In addition to comprehensive adaptive T cell responses, several innate lymphocyte populations seem to target different stages of EBV infection and are compromised in primary immunodeficiencies that render individuals susceptible to symptomatic EBV infection. In this minireview I will high-light the functions of natural killer (NK),  T cells and natural killer T cells (NKT) during innate immune responses to EBV. These innate lymphocyte populations seem to restrict both lytic replication and transforming latent EBV antigen expression. The mechanisms underlying the recognition of these different EBV infection programs by the respective innate lymphocytes are just starting to become unraveled, but will provide immunotherapeutic strategies to target pathologies that are associated with the different EBV infection programs.